PATTERN OF THYROID AUTOANTIBODIES, ESSENTIAL AND TOXIC TRACE ELEMENTS IN VARIOUS THYROID DISORDERS IN NIGERIA
Thyroid disorders are metabolic diseases where autoimmunity has been identified as a major cause. Alteration of balance between certain essential (Copper, Iron, Selenium, Zinc) and toxic (Arsenic, Lead, Cadmium, Nickel) trace elements has a strong role in the pathogenesis of auto- immune thyroid disease but this has received little attention. The imbalance in various thyroid disorders in Nigerian patients was investigated. Two hundred and seventy three (52 males, 221 females) consenting age-matched subjects of 18 to 65 years were consecutively enrolled based on clinical symptoms and thyroid function tests from University College Hospital, Ibadan and Lagos University Teaching Hospital, Lagos,Nigeria. They were divided into four groups: Simple Non-Toxic Goitre (SNTG, n=43), hyperthyroidism thyroidism (HYPERTH, n=79), hypothyroidism (HYPOTH, n=15) and controls (n=136). Socio- demographic characteristics and anthropometric indices were obtained using a structured question- naire. Spot urine samples were collected for determination of iodine status (IOD) using colori- metric method. Blood (10mL) was collected and the plasma was used for determination of Thyroid Function Tests (TFTs) and trace elements. The TFTs: Total Triiodothyronine (T3), Total Thyroxine (T4), Free Triiodothyronine (FT3), Free Thyroxine (FT4), Thyroid Stimulating Hormone (TSH), thyroglobulin, autoantibodies (Antithyroid Peroxidase, TPOAb and Antithyroglobulin, TgAb) were determined using Enzyme - Linked Immunosorbent Assay (ELISA). Trace elements were determined by Atomic Absorption Spectrophotometer (AAS). Data were analysed using Student's t-test, ANOVA and Pearson's correlation at p = 0.05. Among subjects with thyroid disorders, 40.1% and 24.8% were positive for TPOAb and TgAb when compared with controls (8.8% and 5.9%), respectively. Antithyroglobulin was positive in 60% (168.8-92.3 kiu/L) HYPOTH, 24.7% (123.8-22.8 kiu/L) HYPERTH and 14.0% (130.9 - 35.0 kiu/L) SNTG. Significantly reduced levels of Cu (11.9-0.3, 11.8-0.2, 16.1-0.5mol/L), Fe (20.10.5, 19.80.4, 15.00.3 mol/L) and Se (0.50.01, 1.00.1, 0.50.03 mol/L) relative to the controls (16.10.2, 28.70.2, 3.80.03 mol/l); and elevated levels of Cd (0.40.01, 0.40.01, 0.30.03 mol/L), and Pb (1.20.03, 1.20.03, 1.20.04 mol/L) were found in SNTG, HYPERTH and HYPOTH respectively, compared with controls (0.60.01, 0.10.01 mol/L). Thyroglobulin was significantly elevated in HYPERTH, SNTG and HYPO compared with controls, suggesting immune alteration. The FT3 and FT4 were significantly increased in SNTG (3.7-0.02 and 14.9-0.2 pmol/L), HYPERTH (4.4-0.02 and 27.2-0.4 pmol/L) but lowered in HYPOTH (1.1-0.03 and 7.4-0.1 pmol/L) compared with controls (3.6-0.1 pmol/L and 13.10.1 pmol/L). The level of TSH was significantly increased in HYPOTH but decreased in SNTG and HYPERTH compared with controls. Negative correlations were obtained for FT4 and TSH (r = - 0.568); FT3 and TPO (r= - 0.2); TgAb and Zn (r = - 0.3). Positive correlations were found between TPO and As (r = 0.3); IOD and TPO (r = 0.3). Imbalances between essential and toxic trace elements and presence of autoantibodies were among the key mechanisms involved in the pathology of thyroid disorders. Early detection of trace element abnormalities will be useful in overall management of thyroid disorders.